Kluczowe aspekty pozostawania Norwegii poza Unią Europejską - Jeliński, Bohdan (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The EU membership means market integration, new challenges and commercial possibilities for trade and industry across Europe. Outside this process still stays Norway in spite of more than forty years of experiences on this field. This article presents fundamental reasons for this fact. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 183-196